The Effect of the Jigsaw Strategy on Acquiring Geographical Concepts among Second-Grade Intermediate Students - طه, محمد مجيد (Tasnim International Journal for Human, Social and Legal Sciences, 2025)
The study aimed to determine the extent of the impact of applying the Jigsaw strategy in teaching the concepts of geography in the social studies textbook for second intermediate students. The experimental method with partial control based on two groups was adopted, and a sample of 60 students was chosen (30 students for each group). After ensuring that the two groups were equal in intelligence, the topics were taught. Selected subject in geography in the social studies book. The experimental group used the Jigsaw strategy and the control group was taught using traditional methods. A 20-item test was prepared. The results of the study showed the superiority of the experimental group over the control group in testing geographical concepts. The research recommended the necessity of using the Jigsaw strategy in teaching geography to middle school students.